Controlled Generation of Orbital Angular Momentum Beams With Coherent Beam Combining Digital Laser and Liquid-Crystal q-Plate - Corentin Lechevalier; Claude-Alban Ranely-Verge-Depre; Ihsan Fsaifes; Rezki Becheker; Gerben Boer; Jean-Christophe Chanteloup (IEEE Photonics Journal, 2024)
We report on versatile orbital angular momentum beam generation through the association of a 61-channels coherent beam combining digital laser and a liquid-crystal q-plate. Particularly, high-order vortex beams that carry orbital angular momentum are generated with radial, azimuthal and/or circular polarization states. The q-plate is designed and manufactured to sustain high average power ensuring that the vortex spatial mode is preserved. The proposed system offers an extra degree of freedom for various applications requesting beam shaping with specific polarization state.